High-efficiency composite complex absorbent for purification of gypsum acid tail gas and preparation method thereof
Patent Information
- Application Number
- CN202610998296.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-06
- Publication Date
- 2026-09-08
- Estimated Expiration
- 2046-07-06
AI Technical Summary
然而,现有络合吸收剂在实际应用中仍存在诸多不足:一方面,络合体系中的活性金属离子容易被尾气中的氧气氧化而失活,导致吸收效率快速下降;另一方面,络合剂在长期循环使用过程中易发生降解,吸收剂的再生性能差,补充频率高,运行成本难以控制
(1)抗氧化性能显著提升。通过将油溶性受阻酚与亚磷酸酯复配作为芯材,并以乙基纤维素和聚乙烯醇为壁材制备微胶囊,将其引入络合吸收体系中。微胶囊结构可实现对抗氧化组分的控释保护,有效抑制亚铁离子等活性金属中心被尾气中残余氧气氧化失活,从而大幅延长吸收剂的有效使用寿命。
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This invention relates to the field of waste gas treatment technology, and in particular to a highly efficient composite complex absorbent for purifying tail gas from gypsum-based acid production and its preparation method. Background Technology
[0002] In gypsum-based acid production processes, the tail gas typically contains high concentrations of sulfur dioxide (SO2) and other acidic gases. Direct emission without effective treatment not only causes severe environmental pollution but also wastes sulfur resources. Currently, commonly used industrial tail gas desulfurization technologies mainly include wet desulfurization processes such as limestone-gypsum, ammonia, and dual-alkali methods, as well as semi-dry / dry desulfurization technologies such as spray drying and circulating fluidized bed methods. Among these, wet desulfurization is widely used due to its high efficiency and stable operation. However, for gypsum-based acid production tail gas, its gas temperature fluctuates greatly, SO2 concentration ranges widely, and it often contains small amounts of oxygen and other impurities. Traditional desulfurization methods have certain limitations in treating this type of tail gas.
[0003] For example, while the limestone-gypsum process is mature and reliable, it suffers from problems such as high equipment investment, high operating energy consumption, and unstable quality of the byproduct gypsum. Ammonia-based desulfurization faces challenges such as ammonia escape, high absorbent consumption, and system corrosion. In recent years, liquid-phase catalytic oxidation desulfurization technology based on metal complexes has attracted attention. This technology utilizes complexes formed by transition metals such as ferrous ions and ligands to efficiently absorb and oxidize SO2, achieving tail gas purification. However, existing complex absorbents still have many shortcomings in practical applications: on the one hand, the active metal ions in the complex system are easily oxidized and deactivated by oxygen in the tail gas, leading to a rapid decline in absorption efficiency; on the other hand, the complexing agent is prone to degradation during long-term recycling, resulting in poor regeneration performance, high replenishment frequency, and difficulty in controlling operating costs. Furthermore, some absorbents are sensitive to trace impurities in the tail gas, lack adaptability, and are difficult to maintain long-term stable purification effects under the complex operating conditions of gypsum-based acid production tail gas. Therefore, developing a highly efficient, stable, and suitable purification absorbent for the characteristics of gypsum-based acid production tail gas is of significant practical importance.
[0004] Therefore, this invention is proposed. Summary of the Invention
[0005] To address the aforementioned technical problems, this invention provides a highly efficient composite complexing absorbent for purifying tail gas from gypsum-based acid production and its preparation method. This complexing agent exhibits significantly improved antioxidant properties, and its absorption efficiency and stability are effectively enhanced.
[0006] In order to achieve the objective of this invention, the following technical solution is adopted: This invention provides a highly efficient composite complex absorbent for purifying tail gas from gypsum-based acid production, comprising: component A and component B, wherein component A is prepared from the following raw materials in parts by mass: 5-15 parts ferrous salt, 0.5-2 parts manganese salt, 20-40 parts main complexing agent, 5-10 parts auxiliary ligand, 5-15 parts pH buffer, and 50-70 parts deionized water; Component B is prepared from the following raw materials based on the total mass of component A: Core material, accounting for 0.5%-2.0% of the total mass of component A; The wall material is 1-2 times the weight of the core material; The dispersion medium accounts for 0.5%-1% of the wall material mass.
[0007] Furthermore, the primary complexing agent is selected from any one or more of ethylenediaminetetraacetic acid disodium salt or aminotriacetic acid; The auxiliary ligands are selected from amino acids containing thiol groups.
[0008] Furthermore, the amino acid containing a sulfhydryl group is L-cysteine or N-acetylcysteine.
[0009] Furthermore, the ferrous salt is FeSO4·7H2O or FeCl2; the manganese salt is MnSO4 or MnCl2.
[0010] Furthermore, the core material is a compound of oil-soluble hindered phenol and phosphite; The wall material is a mixture of ethyl cellulose and polyvinyl alcohol.
[0011] Furthermore, the oil-soluble hindered phenol is pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], and the phosphite is tris(2,4-di-tert-butylphenyl)phosphite.
[0012] Furthermore, the mass ratio of the oil-soluble hindered phenol to the phosphite is (1:1) to (2:1). The mass ratio of ethyl cellulose to polyvinyl alcohol is 3:1.
[0013] Furthermore, the dispersion medium is Tween 80.
[0014] This invention also provides a method for preparing a highly efficient composite complex absorbent for purifying tail gas from gypsum-based acid production, comprising the following steps: S1. Prepare component A; S2. Prepare component B; S3. Mix component A and component B to prepare a composite complex absorbent.
[0015] Furthermore, S1 specifically includes: S101. Heat deionized water, add the main complexing agent and stir until completely dissolved to obtain a transparent liquid; S102. The manganese salt and ferrous salt are pre-dissolved and kept at the temperature, and then added to the transparent liquid. S103. Under a light-proof or inert gas atmosphere, cool to room temperature, then add auxiliary ligands and stir. Finally, add pH buffer to adjust the pH to 6.5±0.3 to obtain component A.
[0016] Furthermore, S2 specifically includes: S201 and ethyl cellulose are dissolved in a mixture of dichloromethane and anhydrous ethanol. After stirring and dissolving, the molten core material is added to form an oil phase. S202. The mixture of polyvinyl alcohol, dispersion medium and deionized water is heated to 40°C to form an aqueous phase; S203. Under high-speed shearing, the oil phase is added dropwise to the aqueous phase for emulsification, the rotation speed is reduced, and the temperature is raised to 50°C for vacuuming, followed by filtration and drying.
[0017] Furthermore, in step S101, the deionized water is heated to 40°C-50°C.
[0018] Furthermore, the specific heating temperature in S201 is 80-90℃.
[0019] Furthermore, in S203, the high-speed shearing rate is 5000rpm-10000rpm; the speed for reducing the rotation speed is 500rpm.
[0020] The present invention has the following technical effects: (1) Significantly improved antioxidant performance. Microcapsules were prepared by combining oil-soluble hindered phenols with phosphites as the core material and ethyl cellulose and polyvinyl alcohol as the wall material, and introduced into the complexation absorption system. The microcapsule structure can achieve controlled release protection of antioxidant components, effectively inhibit the oxidation and deactivation of active metal centers such as ferrous ions by residual oxygen in the exhaust gas, thereby significantly extending the effective service life of the absorbent.
[0021] (2) Excellent absorption stability and regeneration performance. Component A utilizes the synergistic effect of the main complexing agent and the thiol-containing auxiliary ligand to stably bind ferrous and manganese ions, enhancing the complex's ability to capture and catalytically oxidize SO2. A pH buffer is used to maintain the system pH at approximately 6.5, ensuring the absorption process occurs within the optimal reaction range. Experiments show that the desulfurization efficiency of this absorbent can be maintained above 95% for a long period during continuous operation, and the regeneration replenishment frequency is significantly reduced.
[0022] (3) High adaptability and low operating cost. This absorbent has good tolerance to temperature fluctuations, SO2 concentration changes and trace impurities in gypsum acid production tail gas, and is not prone to degradation or poisoning. The introduction of microcapsules in component B reduces the direct consumption of antioxidants and reduces the amount of complexing agent to be added. The overall operating cost can be reduced by 20% to 30% compared with traditional complexing absorbents. Detailed Implementation
[0023] To make the objectives, technical solutions, and advantages of this invention clearer, the technical solutions of this invention will be clearly and completely described below. Obviously, the described embodiments are only a part of the embodiments of this invention, and not all of them. Based on the embodiments of this invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this invention.
[0024] Firstly, in the gypsum-based sulfuric acid production process, tail gas desulfurization has long faced a core contradiction: maintaining efficient sulfur dioxide absorption capacity while simultaneously addressing the oxidative damage to the absorbent caused by residual oxygen in the tail gas. Existing metal complex absorbents, especially liquid-phase catalytic oxidation systems based on ferrous ions, while capable of rapidly complexing and converting sulfur dioxide, suffer from a fatal weakness: ferrous ions are readily oxidized to ferric iron by oxygen, leading to complex deactivation and a sharp drop in absorption efficiency. This oxidation process is almost unavoidable in oxygen-containing atmospheres, and the tail gas from gypsum-based sulfuric acid production contains a certain proportion of oxygen, with large temperature fluctuations and wide variations in sulfur dioxide concentration, further exacerbating the instability of the complexing system.
[0025] For a long time, existing technologies have attempted to delay the oxidation of ferrous ions by adding free antioxidants. However, free antioxidants are consumed very quickly and require frequent replenishment, which not only increases operating costs but may also introduce side reactions into the system. Meanwhile, the complexing agent itself is prone to degradation during recycling, leading to the precipitation of ferrous ions and causing irreversible failure of the absorbent. Furthermore, single ferrous complexes have limited absorption capacity and poor regeneration performance, making it difficult to maintain a desulfurization rate of over 95% during long-term continuous operation.
[0026] Therefore, the present invention aims to construct a composite absorption system that can efficiently capture and catalytically oxidize sulfur dioxide, resist oxygen attack for a long time, maintain the stable valence state of active metal ions, and has excellent regeneration performance and low operating cost.
[0027] Based on this, the present invention provides a highly efficient composite complex absorbent for purifying tail gas from gypsum-based acid production, comprising: component A and component B, wherein component A is prepared from the following raw materials in parts by mass: 5-15 parts ferrous salt, 0.5-2 parts manganese salt, 20-40 parts main complexing agent, 5-10 parts auxiliary ligand, 5-15 parts pH buffer, and 50-70 parts deionized water; Component B is prepared from the following raw materials based on the total mass of component A: Core material, accounting for 0.5%-2.0% of the total mass of component A; The wall material is 1-2 times the weight of the core material; The dispersion medium accounts for 0.5%-1% of the wall material mass.
[0028] Component A provides active metal ions (ferrous and manganese salts), the main complexing agent, auxiliary ligands, a pH buffer, and deionized water, forming the main liquid-phase absorbent. Component B, based on the total mass of component A, introduces a core material (antioxidant), wall material, and dispersion medium, achieving controlled release of the antioxidant components through microcapsules. This dual-component design allows for relatively independent yet synergistic absorption and protection functions, preventing the antioxidant from dissolving directly in the system and being rapidly consumed, thus extending the absorbent's effective lifespan. The addition of manganese salt forms a bimetallic synergy with ferrous salt, enhancing the catalytic oxidation efficiency of sulfur dioxide. The main complexing agent and auxiliary ligand work together to stabilize the metal ions, improving anti-precipitation capabilities.
[0029] In some embodiments, the primary complexing agent is selected from any one or more of ethylenediaminetetraacetic acid disodium salt or aminotriacetic acid; The auxiliary ligands are selected from amino acids containing thiol groups.
[0030] The primary complexing agent is further specified as disodium ethylenediaminetetraacetate (EDTA) or aminotriacetic acid (ATA), and the auxiliary ligand is a thiol-containing amino acid (such as L-cysteine). ETA or ATA provides strong coordination ability, stabilizing ferrous and manganese ions; the thiol group (-SH) in the amino acid can form additional coordination with metal ions and also possesses some reducing properties, which can inhibit oxidation to a certain extent. This design enhances the thermodynamic stability of the complex, reduces the tendency of metal ions to hydrolyze and precipitate, and the auxiliary ligand can improve the initial antioxidant capacity of the absorbent.
[0031] In some embodiments, the thiol-containing amino acid is L-cysteine or N-acetylcysteine.
[0032] In some embodiments, the ferrous salt is FeSO4·7H2O or FeCl2; the manganese salt is MnSO4 or MnCl2.
[0033] In some embodiments, the core material is a compound of oil-soluble hindered phenol and phosphite; The wall material is a mixture of ethyl cellulose and polyvinyl alcohol.
[0034] The core material is a blend of oil-soluble hindered phenols and phosphites, while the wall material is a mixture of ethyl cellulose and polyvinyl alcohol. Hindered phenols are chain-terminated antioxidants, and phosphites are peroxide decomposers; their combination produces a synergistic antioxidant effect. Ethyl cellulose forms the microcapsule framework, and polyvinyl alcohol acts as an emulsifying stabilizer and film-forming aid, together constituting the encapsulation layer. This method can encapsulate liquid or oil-soluble antioxidants into solid microcapsules, achieving sustained-release and controlled-release, avoiding burst release waste. The wall material slowly swells or ruptures in the aqueous phase of the absorbent, allowing the core material to be released as needed, continuously protecting ferrous ions.
[0035] In some embodiments, the oil-soluble hindered phenol is pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], and the phosphite is tris(2,4-di-tert-butylphenyl)phosphite.
[0036] In some embodiments, the mass ratio of the oil-soluble hindered phenol to the phosphite is (1:1) to (2:1). The mass ratio of ethyl cellulose to polyvinyl alcohol is 3:1.
[0037] Optimized proportions maximize the synergistic effect of antioxidants; the wall material ratio ensures appropriate mechanical strength and release rate of the microcapsules. A balance is maintained between antioxidant efficiency and release characteristics, avoiding release that is too fast or too slow.
[0038] In some embodiments, the dispersion medium is Tween 80.
[0039] Secondly, the present invention also provides a method for preparing a highly efficient composite complex absorbent for purifying tail gas from gypsum-based acid production, comprising the following steps: S1. Prepare component A; S2. Prepare component B; S3. Mix component A and component B to prepare a composite complex absorbent.
[0040] Stepwise preparation allows for separate control of the coordination reaction conditions of component A and the microcapsule formation conditions of component B, followed by simple mixing before use. The process is simple, suitable for industrial production, and components A and B can be stored separately and mixed on-site during use, avoiding premature release of microcapsules or deterioration of component A during long-term storage.
[0041] In some embodiments, S1 specifically includes: S101. Heat deionized water, add the main complexing agent and stir until completely dissolved to obtain a transparent liquid; S102. The manganese salt and ferrous salt are pre-dissolved and kept at the temperature, and then added to the transparent liquid. S103. Under a light-proof or inert gas atmosphere, cool to room temperature, then add auxiliary ligands and stir. Finally, add pH buffer to adjust the pH to 6.5±0.3 to obtain component A.
[0042] Heating promotes the dissolution of the main complexing agent; adding the metal salt first allows it to be complexed immediately, preventing the hydrolysis of free metal ions; avoiding light or using an inert atmosphere prevents the oxidation of ferrous ions; finally, the auxiliary ligand and pH buffer are added to prevent the auxiliary ligand from oxidizing at high temperatures or reacting prematurely with metal ions. This step ensures that the components in component A are homogeneous and stable, that ferrous ions are preserved in their divalent form, and that the pH value is within the optimal absorption range (around 6.5), which is beneficial for the absorption and catalytic conversion of sulfur dioxide.
[0043] In some embodiments, S2 specifically includes: S201 and ethyl cellulose are dissolved in a mixture of dichloromethane and anhydrous ethanol. After stirring and dissolving, the molten core material is added to form an oil phase. S202. The mixture of polyvinyl alcohol, dispersion medium and deionized water is heated to 40°C to form an aqueous phase; S203. Under high-speed shearing, the oil phase is added dropwise to the aqueous phase for emulsification, the rotation speed is reduced, and the temperature is raised to 50°C for vacuuming, followed by filtration and drying.
[0044] High-speed shearing forms an O / W emulsion, followed by heating and vacuuming to evaporate dichloromethane, causing ethyl cellulose to precipitate and solidify, forming microcapsules that encapsulate the core material. The resulting microcapsules are uniform in size and completely encapsulated. The dispersion medium reduces interfacial tension and improves emulsion stability; the solvent evaporation method is gentle and does not damage the activity of the core material.
[0045] In some embodiments, in step S101, deionized water is heated to 40°C-50°C.
[0046] In some embodiments, the specific heating temperature in S201 is 80-90°C.
[0047] In some embodiments, in S203, the high-speed shearing rate is 5000rpm-10000rpm; the speed for reducing the rotation speed is 500rpm.
[0048] The following is a detailed explanation using specific embodiments: Example 1 Component A: Weighing: FeSO4·7H2O 12g, MnSO4·H2O 1.2g, disodium ethylenediaminetetraacetate (EDTA-2Na) 35g, L-cysteine 7g, KH2PO4 3g, K2HPO4·3H2O 7g, deionized water 34.8g.
[0049] Component B: Pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] 0.9g, Tris(2,4-di-tert-butylphenyl) phosphite 0.6g, Ethyl cellulose (methoxy content 48.0%-49.5%, viscosity specification 10-20 mPa·s) 1.8g, Polyvinyl alcohol (degree of hydrolysis 87%-89%) 0.6g, Tween 80 0.019g.
[0050] Deionized water was injected into a jacketed stirred reactor, and the temperature was turned on to 45°C. EDTA-2Na was slowly added to the water at a stirring speed of 300 rpm and stirred for 30 minutes until the solution was colorless and transparent with no visible particles, thus obtaining a transparent liquid.
[0051] FeSO4·7H2O and MnSO4·H2O were pre-dissolved in deionized water at 40℃. Under a nitrogen atmosphere, the temperature was maintained, and then the mixed metal salt solution was added dropwise to the transparent liquid at a uniform rate using a peristaltic pump, which was completed within 15 minutes.
[0052] Cool the reaction solution to 25°C, add L-cysteine under light-protected conditions, continue stirring for 15 minutes, and finally add KH2PO4 and K2HPO4·3H2O and stir until completely dissolved. The pH is calibrated to 6.53 using a pH meter to obtain 100g of component A. Store component A in a storage tank under light-protected conditions.
[0053] Ethyl cellulose was dissolved in a mixture of dichloromethane and anhydrous ethanol (volume ratio 2:1), and after stirring to dissolve, pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] and tris(2,4-di-tert-butylphenyl) phosphite were added at 80-90℃.
[0054] Dissolve polyvinyl alcohol and Tween 80 in 100 mL of deionized water and heat to 40 °C to dissolve.
[0055] The oil phase was slowly added to the aqueous phase at 10,000 rpm using a high-speed shear press, and emulsified for 15 minutes to obtain an O / W emulsion. The mixture was then switched to magnetic stirring, heated to 48°C, and slowly stirred at 500 rpm for 4 hours to allow complete evaporation of dichloromethane and precipitation of ethyl cellulose to form microspheres. The microspheres were filtered, washed three times with deionized water, and dried under vacuum at 25°C for 12 hours to obtain white powdery microcapsules, yielding 1.96 g of component B.
[0056] Component A and component B are mixed to obtain a composite complex absorbent.
[0057] Example 2 The specific preparation method is consistent with that in Example 1, except that disodium ethylenediaminetetraacetate is replaced with an equal mass of aminotriacetic acid; and L-cysteine is replaced with an equal mass of N-acetylcysteine. At this time, 2g of component B is obtained, which is mixed with 100g of component A to prepare a composite complex absorbent.
[0058] Experiment Example 1: Desulfurization Performance Test Set up groups: Example 1, Example 2; Comparative Example 1: Using only component A from Example 1; Comparative Example 2: Weigh 12 g of FeSO4·7H2O and 35 g of disodium ethylenediaminetetraacetate (EDTA-2Na), dissolve them in 53 g of deionized water, stir until completely dissolved, and adjust the pH to 6.5±0.3 with pH buffer.
[0059] A laboratory-scale simulated tail gas absorption device was used, with a packed absorption tower inner diameter of 50 mm and a packing height of 500 mm. Simulated gypsum-based acid production tail gas was prepared with an SO2 concentration of 2000 mg / m³. 3 The O2 content was 5%, N2 was used as the balance gas, and the gas flow rate was 1.0 L / min. The absorbent volume was 500 mL, and the absorption temperature was 45℃. The SO2 concentration in the exhaust gas was continuously monitored online using non-dispersive infrared absorption spectrometry.
[0060] The above experiments were conducted in groups under the above experimental conditions, and the initial desulfurization rate and the desulfurization rate after continuous operation for 12 h and 24 h were recorded. The experimental results are shown in Table 1.
[0061] Table 1: Desulfurization performance test results The initial desulfurization rates of Examples 1 and 2 were both above 98%, significantly higher than those of the comparative examples. After 24 hours of continuous operation, the desulfurization rate of Example 1 remained at 97.8%, while that of Comparative Examples 1 and 2 decreased to 68.4% and 61.2%, respectively. This indicates that the prepared absorbent has excellent long-term desulfurization stability, and the microcapsules of component B effectively inhibited the oxidative deactivation of active metal ions.
[0062] Experiment Example 2: Antioxidant Performance Test The experimental groups are the same as in Experiment 1.
[0063] Take 200 mL of each absorbent and place it in a three-necked flask. Purge with air (flow rate 0.5 L / min) and maintain the temperature at 45℃ with stirring. Take samples every 2 hours to determine the Fe content in the solution. 2+ Concentration (using the o-phenanthroline spectrophotometric method) was used to calculate Fe. 2+ Retention rate (Fe) 2+ Retention rate = Current Fe 2+Concentration / Initial Fe 2+ (Concentration × 100%), continuously monitored for 8 h, and the experimental results are shown in Table 2.
[0064] Table 2: Results of Antioxidant Performance Tests Example 1: Fe after 8 h of air oxidation 2+ The retention rate remained as high as 93.1%, while Comparative Examples 1 and 2 had only 51.7% and 43.6%, respectively. This indicates that the hindered phenol / phosphite antioxidant encapsulated in the microcapsules of this invention can be continuously released, effectively protecting ferrous ions and significantly enhancing the antioxidant capacity of the absorbent.
[0065] Experiment Example 3: Cyclic Regeneration Performance Test An absorption-desorption cycle device was used. The absorption conditions were the same as in Experiment 1. After absorption saturation, the absorbent was heated to 60°C, and N2 gas was introduced to desorb SO2 (desorption time 30 min). The desorbed absorbent was then replenished with a small amount of water to restore its original volume before entering the next cycle. The desulfurization efficiency was measured every 5 cycles, and a total of 30 cycles were performed. The experimental results are shown in Table 3.
[0066] Table 3: Results of Cyclic Regeneration Performance Test After 30 cycles of absorption-regeneration, Example 1 maintained a desulfurization rate of over 95%, while Comparative Examples 1 and 2 decreased to 51.2% and 43.8%, respectively. This demonstrates that the absorbent of the present invention exhibits excellent regeneration performance, minimal degradation of the complexing agent, and low loss of active components, making it suitable for continuous industrial operation.
[0067] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the technical solutions of the embodiments of the present invention.
Claims
1. A high-efficiency composite complexing absorbent for purifying tail gas from gypsum-based acid production, characterized in that, include: Component A and Component B, by mass parts, Component A is obtained from the following raw materials: 5-15 parts ferrous salt, 0.5-2 parts manganese salt, 20-40 parts main complexing agent, 5-10 parts auxiliary ligand, 5-15 parts pH buffer, and 50-70 parts deionized water; Component B is prepared from the following raw materials based on the total mass of component A: Core material, accounting for 0.5%-2.0% of the total mass of component A; The wall material is 1-2 times the weight of the core material; The dispersion medium accounts for 0.5%-1% of the wall material mass; The primary complexing agent is selected from any one or more of the following: disodium ethylenediaminetetraacetate or aminotriacetic acid; The auxiliary ligand is selected from amino acids containing thiol groups; The core material is a compound of oil-soluble hindered phenol and phosphite; The wall material is a mixture of ethyl cellulose and polyvinyl alcohol.
2. The high-efficiency composite complex absorbent for purifying tail gas from gypsum-based acid production according to claim 1, characterized in that, The mass ratio of the oil-soluble hindered phenol to the phosphite is (1:1) to (2:1). The mass ratio of ethyl cellulose to polyvinyl alcohol is 3:
1.
3. A method for preparing a high-efficiency composite complex absorbent for purifying tail gas from gypsum-based acid production, as described in any one of claims 1-2, characterized in that, The steps include the following: S1. Prepare component A; S2. Prepare component B; S3. Mix component A and component B to prepare a composite complex absorbent.
4. The preparation method of the high-efficiency composite complex absorbent for purifying tail gas from gypsum-based acid production according to claim 3, characterized in that, S1 specifically includes: S101. Heat deionized water, add the main complexing agent and stir until completely dissolved to obtain a transparent liquid; S102. The manganese salt and ferrous salt are pre-dissolved and kept at the temperature, and then added to the transparent liquid. S103. Under a light-proof or inert gas atmosphere, cool to room temperature, then add auxiliary ligands and stir. Finally, add pH buffer to adjust the pH to 6.5±0.3 to obtain component A.
5. The preparation method of the high-efficiency composite complex absorbent for purifying tail gas from gypsum-based acid production according to claim 3, characterized in that, S2 specifically includes: S201 and ethyl cellulose are dissolved in a mixture of dichloromethane and anhydrous ethanol. After stirring and dissolving, the molten core material is added to form an oil phase. S202. The mixture of polyvinyl alcohol, dispersion medium and deionized water is heated to 40°C to form an aqueous phase; S203. Under high-speed shearing, the oil phase is added dropwise to the aqueous phase for emulsification, the rotation speed is reduced, and the temperature is raised to 50°C for vacuuming, followed by filtration and drying.
6. The preparation method of the high-efficiency composite complex absorbent for purifying tail gas from gypsum-based acid production according to claim 3, characterized in that, In step S101, deionized water is heated to 40°C-50°C.
7. The preparation method of the high-efficiency composite complex absorbent for purifying tail gas from gypsum-based acid production according to claim 5, characterized in that, In S203, the high-speed shearing rate is 5000rpm-10000rpm; the speed of the reduced rotation speed is 500rpm.
Citation Information
Patent Citations
Bimetallic FMG desulfurizer for wet oxidation desulfurization
CN113637503A
Liquid Iron Chelate Compositions for Desulfurization and Preparation Methods Thereof
KR101774170B1